Serial Editions in the Publisher Repertoire of Children’s Books of Udmurtia of the XIX–XXI Centuries - I. F. Pavlova (Библиосфера, 2022)
The sociocultural aspect of modern national book publishing is associated with the changing role of the book in society. A study of the development of a children’s book in Udmurtia in 1847–2010, an analysis of its repertoire, which includes more than 3,000 bibliographic entries, showed from various aspects that in the period under review, a children’s book develops very unevenly. No one has studied the trends in the genesis of serial publications for children in Udmurtia. An analysis of this problem will help to identify the direction of the publishing repertoire, the target and readership of a children’s book in different periods of its development, as well as enrich knowledge on the history of the region’s books, and increase interest in the national and domestic culture of the republic.The purpose of this article is to study the trends in the development of book series for children and youth of the Udmurt Republic throughout its historical existence in the 19th – early 21st centuries.The study of the repertoire of children’s books in Udmurtia, as a fundamental basis for the study of the cultural development of the people over a large historical period, made it possible to identify 80 series addressed to children of all ages, from preschool to high school students. We have considered all publications included in a certain series; its target and readership; the number of series in each historical period of time, the number of publications and the total circulation included in a certain series are determined; the origins of the series in a certain historical period are traced within the framework of the events that took place at that time and appropriate conclusions are drawn. The practical significance of such a study lies in the fact that it allows a comprehensive study of the process of regional and national book publishing in Udmurtia, taking into account the experience of the past and improving the publishing repertoire of the present.